The IT/digital legal companion a comprehensive business guide to software, Internet, and IP law : includes contracts and web forms - Landy, Gene K.; Mastrobattista, Amy J. (Amsterdam ; Boston : Syngress/Elsevier, 2008)
To compete effectively in digital business markets, you need to understand how the law affects your digital technology business. The contents include detailed plain English business and legal guidance on: * Securing Intellectual Property for Digital Business * Digital Contract Fundamentals * Open Source Rules and Strategies * Development, Consulting and Outsourcing * Software as a Service * Business Software Licensing, Partnering and Distribution * Web and Internet Agreements * Privacy on the Internet * Digital Multimedia Content Clearance and Distribution * IT Standards * Web and Mobile Technology and Content Deals * Video Game Development Deals * International Distribution * User-Created Content, Mash-ups, MMOGs and Web Widgets * And Much More Comprehensive Business and Legal Guidance including * Securing Intellectual Property for Digital Business * Digital Contract Fundamentals * Open Source Rules and Strategies * Development, Consulting and Outsourcing * Software as a Service * Business Software Licensing, Partnering, and Distribution * Web and Internet Agreements * Privacy on the Internet * Digital Multimedia Content Clearance and Distribution * IT Standards * Video Game Development and Content Deals * International Distribution * User-Created Content, Mash-Ups, MMOGs, and Web Widgets * And Much More Key Features: * Up-to-the-Moment Legal Guide * In Plain English * Includes 38 Contract and Web Forms in the Book and Online.
Acknowledgement by Gene Landy -- A Note from the Authors -- About the Authors -- About the Authors' Law Firm -- Form Downloading Instructions -- Chapter 1 Introduction: Using this Book to Build Value -- Chapter 2 Digital Copyright Basics -- Chapter 3 Copyrights on the Internet, for Software Protection and Around the World -- Chapter 4 Tradmarks and Domain Names -- Chapter 5 Patents and Digital Technology Companies -- Chapter 6 Trade Secrets and Non-Disclosure Agreements -- Chapter 7 Confidentiality, Rights Transfer, and Non-Competition Agreements for Employees -- Chapter 8 Introduction to Digital Product and Service Contracts -- Chapter 9 A Pragmatic Guide to Open Source -- Chapter 10 IT Services--Development, Outsourcing, and Consulting -- Chapter 11 Beta Test Agreements -- Chapter 12 Commercial End-User Agreements -- Chapter 13 Software as a Service (SaaS) -- Chapter 14 Commercial Distribution--Part I -- Chapter 15 Commercial Distribution--Part II -- Chapter 16 Clickwraps and Browsewraps -- Chapter 17 Terms of Use for Web Sites and Online Applications -- Chapter 18 Privacy and Use of Personal Data -- Chapter 19 Digital Technology Standards--Opportunities, Risks, and Strategies -- Chapter 20 Content for Digital Media -- Chapter 21 Deals in the Web and Mobile Value Chains -- Chapter 22 Video Games! Developing Games and Doing Deals -- Chapter 23 Going Global--Doing Business in World Markets -- Chapter 24 United States Export Controls -- Chapter 25 Proactive Management of Your Legal Affairs -- Forms Appendix -- Index.
Includes index.
Keywords: Internet -- Law and legislation -- United States; Electronic commerce -- Law and legislation -- United States; Data protection -- Law and legislation -- United States; Intellectual property -- United States; Information technology -- United States; United States; Electronic books